1980
DOI: 10.1093/ajcp/74.6.842
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Pneumonia Caused by a New Acid-fast Bacterium

Abstract: An 80-year-old black woman with a clinical diagnosis of unclassified malignant lymphoproliferative disease experienced acute pneumonia four days after chemotherapy was begun. Open lung biopsy revealed acute suppurative pneumonia with dense neutrophilic alveolar infiltrates but without granulomas or caseous necrosis. Numerous intra- and extracellular gram-negative bacilli were present, some of which were acid-fast. Routine bacterial, fungal, and mycobacterial cultures were negative. The organism was successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Legionellae do not stain with hematoxylin-eosin in formalin-fixed paraffin tissue sections but can be demon- strated easily with Dieterle or Warthin-Starry silver impregnation procedures. 11 While original descriptions of the agent of Legionnaires' disease did not include acid fastness as a characteristic, 12 subsequent reports of opportunistic pneumonia likely secondary to Legionellae were reported by Rogers et al 13 and Talamo et al 14 In both series of patients, the infected individuals were severely ill, immunocompromised patients (four were renal-transplant patients), similar to the case presented in this report.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Legionellae do not stain with hematoxylin-eosin in formalin-fixed paraffin tissue sections but can be demon- strated easily with Dieterle or Warthin-Starry silver impregnation procedures. 11 While original descriptions of the agent of Legionnaires' disease did not include acid fastness as a characteristic, 12 subsequent reports of opportunistic pneumonia likely secondary to Legionellae were reported by Rogers et al 13 and Talamo et al 14 In both series of patients, the infected individuals were severely ill, immunocompromised patients (four were renal-transplant patients), similar to the case presented in this report.…”
Section: Discussionsupporting
confidence: 64%
“…Similar observations were reported by Schwebke et al 9 Most L. micdadei, when visualized in clinical specimens, are acid-fast when stained by a modified Ziehl-Neelsen, Kinyoun, or Fite Stain. 13,14,16,17 Those authors concluded that L. micdadei should be considered and included in the empiric coverage when the acid-fast smear is positive, pending confirmation by specific fluorescent stains.…”
Section: Discussionmentioning
confidence: 99%
“…are weakly acid fast, so that culture is critical for diagnosis. Legionella micdadei also appears acid fast in tissue, a characteristic most frequently demonstrated with Kinyoun and Fite stains and less often with Ziehl-Neelsen stain (133,152,170,196). For detection of all species of Legionella, the Wolbach modification of Giemsa stain appears to provide consistently good staining of the bacterial cells (59).…”
Section: Detection In Tissue Sectionsmentioning
confidence: 94%
“…Although other respiratory pathogens, such as Nocardia, Actinomyces, Rhodococcus, Legionella micdadei , and cyst of Cryptosporidium can cause positive AFB staining (12, 13, 23, 24), and one should be aware of the potential for misdiagnosis because of these organisms (25, 26), we found no false positive AFB smears caused by these organisms of the 447 sputa with positive AFB smears screened over two years. In this context, we believe that a false positive AFB smear is rarely caused by a micro-organism other than mycobacteria.…”
Section: Discussionmentioning
confidence: 61%
“…A positive AFB smear resulting from other bacteria that may have a positive AFB smear, such as Nocardia, Actinomyces, Rhodococcus, Legionella micdadei or cysts of Cryptosporidium species (12, 13). …”
Section: Methodsmentioning
confidence: 99%